Effect of young corn (zea mays l.) powder incorporation in biscuits and muffins on physicochemical properties, sensorial acceptability and glycemic index values - Che Mohd Zin, Che Anis Jauharah (2015)
This study was conducted to develop biscuits and muffins incorporated with young corn powder (YCP) and to evaluate the effect on nutritional compositions, instrumental texture profile, sensorial acceptability and glycemic index (GI). Fresh young corn was dried, ground into powder and added in biscuit and muffin formulations at concentrations of 0, 10, 20 and 30%. Results showed incorporation of YCP in biscuits and muffins had significantly increased protein and total dietary fiber contents. Physical analysis of biscuits demonstrated that there were no significant differences in hardness and fracturability attributes as the level of YCP incorporation increased. There was no statistically significant difference (p>0.05) in diameter between biscuits with YCP and biscuits without YCP. Influences of YCP on spread ratio of biscuits were significant only at 30% level of incorporation. Meanwhile, for muffins, incorporation of YCP did not significantly increase the hardness at level of 10 and 20%. Springiness of muffins with up to 20% level of YCP incorporation did not differ significantly from 0% YCP muffins. It was noted that muffins with YCP was less cohesive than muffins without YCP, which indicates that the former was better than the latter. Chewiness of muffins was not substantially affected by YCP. Sensory acceptability test revealed that the mean score for aroma, appearance, crispiness and flavour of biscuits added with 10% YCP was better than biscuits without YCP. In addition, muffins formulated with YCP, regardless of level of incorporation, received better acceptability score for appearance, texture, taste and flavour compared to muffins without YCP. Based on sensorial acceptability results, two formulations of biscuits (0 and 10% YCP) and two formulations of muffins (0 and 30% YCP) were selected for GI testing. It was found that the GI of biscuits with 10% YCP was 46 ± 11 while the 0% YCP biscuits was 61 ± 13. Muffins with 0 and 30% YCP recorded GI values of 58 ± 6 and 57 ± 9, respectively. Addition of YCP had reduced the GI values of biscuits and muffins and significantly reduced the postprandial peak glucose responses. The results of this study showed that biscuits and muffins added with YCP have a low and intermediate GI with acceptable physicochemical properties.